Magma–Shale Interaction in Large Igneous Provinces: Implications for Climate Warming and Sulfide Genesis. (8th September 2022) - Deegan, Frances M; Bédard, Jean H; Grasby, Stephen E; Dewing, Keith; Geiger, Harri; Misiti, Valeria; Capriolo, Manfredo; Callegaro, Sara; Svensen, Henrik H; Yakymchuk, Chris; Aradi, László E; Freda, Carmela; et al.
Abstract: Large igneous provinces (LIPs) whose magma plumbing systems intersect sedimentary basins are linked to upheavals of Earth's carbon and sulfur cycles and thus climate and life history. However, the underlying mechanistic links between these phenomena are elusive. We address this knowledge gap through short time-scale petrological experiments (1200°C and 150 MPa) that explore interaction between basaltic melt and carbonaceous shale (mudstone) using starting materials from the Canadian High Arctic LIP and the Sverdrup Basin in which it intrudes. Here we show that entrainment of shale xenoliths in basaltic melt causes shale to shatter due to incipient thermal stress and devolatilization, which accelerates assimilation by increasing reactive surface area. Shale assimilation therefore facilitates transfer of sediment-derived volatile elements to LIP magma plumbing systems, whereupon carbon dominates the vapor phase while sulfur is partitioned into sulfide melt droplets. This study reveals that although carbon and sulfur are efficiently mobilized as a consequence of shale assimilation, sulfides can sequester sulfur—an important climate cooling agent—thus enhancing net emissions of climate warming greenhouse gases by shale-intersecting LIPs.